2017
DOI: 10.1002/jcb.26252
|View full text |Cite|
|
Sign up to set email alerts
|

Retracted: microRNA‐145‐3p inhibits non‐small cell lung cancer cell migration and invasion by targeting PDK1 via the mTOR signaling pathway

Abstract: The mammalian target of rapamycin (mTOR) pathway is dysregulated in more than 50% of all human malignancies and is a major target in cancer treatment. In this study, we explored the underlying mechanism involving microRNA-145-3p (miR-145-3p) in the development and progression of non-small cell lung cancer (NSCLC) by targeting PDK1 via the mTOR signaling pathway. NSCLC tissues and adjacent normal tissues were obtained from 83 NSCLC patients. miR-145-3p, PDK1, and mTOR levels were determined by quantitative r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
23
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 26 publications
(24 citation statements)
references
References 35 publications
(72 reference statements)
1
23
0
Order By: Relevance
“…Among them, miR-145 plays a suppressive role in tumor progression and is involved in tumorigenesis. Furthermore, miR-145 with anticancer effect was identified in ovarian carcinoma ( 23 ), colorectal carcinoma ( 24 ) and non-small cell lung cancer ( 25 ). The same conclusion for BC was obtained in this study.…”
Section: Discussionmentioning
confidence: 99%
“…Among them, miR-145 plays a suppressive role in tumor progression and is involved in tumorigenesis. Furthermore, miR-145 with anticancer effect was identified in ovarian carcinoma ( 23 ), colorectal carcinoma ( 24 ) and non-small cell lung cancer ( 25 ). The same conclusion for BC was obtained in this study.…”
Section: Discussionmentioning
confidence: 99%
“…Our previous studies demonstrated that antitumor miR-145-3p directly targeted oncogenes, e.g., MTDH in lung adenocarcinoma, UHRF1 in bladder cancer, MYO1B in head and neck cancer and MELK, NCAPG, BUB1 and CDK1 in prostate cancer (17)(18)(19)(20). Another group demonstrated that miR-145-3p inhibited cell growth, motility and chemotaxis in non-small cell lung cancer by targeting pyruvate dehydrogenase kinase 1 through suppressing the mechanistic target of rapamycin pathway (37). These findings indicated that antitumor miR-145-3p is associated with cancer pathogenesis.…”
Section: Discussionmentioning
confidence: 99%
“…miRNAs have been reported to modulate cancer progression and are considered as potential biomarkers for diagnosis, pathogenesis and progression prediction, as well as therapy in numerous cancers, including lung cancer, breast cancer, thyroid carcinoma and colorectal cancer (13)(14)(15)(16). Particularly, miRNA-145 exerts a regulatory effect on multiple types of human tumors, including colorectal cancer, non-small cell lung cancer, pancreatic cancer and oral cancer (17)(18)(19)(20). Nevertheless, the underlying mechanism of miRNA-145-mediated modulation of migration and invasion of BC cells remains to be elucidated.…”
Section: Introductionmentioning
confidence: 99%